BAGAIMANA ANALISIS PENDAPATAN DAN BIAYA RELEVAN ATAS BISNIS ONLINE? - Setiawan, Temy; Anggriawan, Denny (Coopetition : Jurnal Ilmiah Manajemen, 2018)
The development of technology and the increasing use of Internet network in the society today has an impact on consumer behavior. Businesses that used to be conventional or offline are now turning to online business, which makes it easier for consumers to be able to conduct business transactions without any limitations of space and time. This study aims to determine the increase in operating income with offline switch to online with the analysis of revenue and relevant costs. This research is descriptive qualitative research. The subject of the research is the Hproject Store. The data used are primary data and secondary data. Data collection techniques with offline store observations and online stores, interviews with owners and employees and documentation of the accounting records. Based on the results of research indicated that switching offline business to online can increase operating profit based on revenue analysis and cost relevant for tactical decision making. The contribution of this research is able to indicate that one of technique in increasing profit is by utilizing technology and network in doing business. In addition, this study can provide consideration of financial analysis techniques before tactical decision making on business techniques.